Holistic Analysis of Coronavirus Literature: A Scientometric Study of the Global Publications Relevant to SARS-CoV-2 (COVID-19), MERS-CoV (MERS) and SARS-CoV (SARS) - Şenel, Engin (Disaster Med Public Health Prep, 2020)
OBJECTIVES: In late December 2019, a cluster of patients with pneumonia caused by an unknown pathogen was reported from Wuhan, Hubei Province, China. The pathogen has been identified as a novel coronavirus, severe acute respiratory syndrome 2 (SARS-CoV-2) and the disease has been named as coronavirus disease 2019 (COVID-19). The objective of this study was to perform the first holistic scientometric evaluation of coronavirus publications. METHODS: Our main source for this study was Web of Science Collection database. All items published between 1980 and 2019 were included. A distribution map of global production in coronavirus literature and scientometric networks were generated. RESULTS: The United States, China, Germany, the United Kingdom, and Netherlands were the most productive countries. Publications in coronavirus literature have been produced from almost every country in the world, except for some countries in Asia and Africa. CONCLUSION: While in the 1980s, the United States and developed countries from Europe were major source countries and the virus was identified only as an animal disease in the literature and its biological and genetic structure was investigated, in the 2000s, China became a major contributor of coronavirus literature because the SARS outbreak originated from southern China. Almost all most-cited publications in this period are related to SARS and the ACE2 protein.